2015
DOI: 10.1097/ta.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Damage-control resuscitation increases successful nonoperative management rates and survival after severe blunt liver injury

Abstract: Therapeutic/care management, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 33 publications
(35 reference statements)
1
47
1
3
Order By: Relevance
“…23,24 Energy-related neurochemical dysregulation in TBI + HS is likely a major factor contributing to worse neurologic outcomes. 25 Therefore, principles of damage-control resuscitation, which include permissive hypotension, 4,5,9 require further study in patients with TBI+HS, since a higher mean arterial pressure (>70-mm Hg) may result in better cerebral blood flow and cerebral mitochondrial function. 26 Speed of resuscitation may also be imperative for protecting brain function; animal models using a stepwise ratio-guided protocol with FFP (compared to a bolus protocol) have demonstrated a neuroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 Energy-related neurochemical dysregulation in TBI + HS is likely a major factor contributing to worse neurologic outcomes. 25 Therefore, principles of damage-control resuscitation, which include permissive hypotension, 4,5,9 require further study in patients with TBI+HS, since a higher mean arterial pressure (>70-mm Hg) may result in better cerebral blood flow and cerebral mitochondrial function. 26 Speed of resuscitation may also be imperative for protecting brain function; animal models using a stepwise ratio-guided protocol with FFP (compared to a bolus protocol) have demonstrated a neuroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…15,22,30,32,33 Ratio-guided resuscitation with fresh frozen plasma (FFP) may have beneficial effects for patients with TBI + HS, 15 including fewer inflammatory complications. 5,6,9 In experimental large animal studies, early administration of FFP reduced the size of brain lesions, decreased cerebral edema, and substantially attenuated the degree of neurological impairment. 32,34 Benefits of FFP resuscitation may be related to gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrestha et al have shown increased likelihood of successful non-operative management and survival in civilian patients with high grade liver injuries after blunt trauma. 64 In the military setting, soldiers injured in combat are also surviving with more severe injuries after implementation of DCR. 65 Based on these studies, the ACS TQIP Massive Transfusion in Trauma Guidelines recommend DCR in patients who meet MTP triggers (see comment 1) (Table 2)…”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 99%
“…In addition, DCR may decrease the surgical hemostatic requirement in severely injured patients. A retrospective study showed an increase in the success rate of nonoperative management from 54 to 74% for grades IV and V severe blunt liver injury after the implementation of DCR [100]. DCR may herald the beginning of the end for DCS [98].…”
Section: Changes Of Surgical Strategy In Dcrmentioning
confidence: 99%